2009
DOI: 10.1086/593111
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Trait Diversification and Design in Seven Rare Taxa of the HawaiianPlantagoRadiation

Abstract: Linkages among leaf traits and environment have most often been tested across communities but infrequently within lineages. We studied seven endemic Hawaiian Plantago taxa radiated across elevations, climates, and habitats. We grew plants of six taxa in controlled conditions for 1-2 yr and collected leaves from a seventh in the field. For all taxa, we measured 46 leaf traits and tested hypotheses for trait-environment and trait-trait associations. Because of the rarity of the study plants, our study included l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
125
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 86 publications
(142 reference statements)
14
125
1
2
Order By: Relevance
“…Notably, genus-by-genus analyses produced comparable patterns, as did phylogenetically controlled tests within lineages for Acer, Plantago and Viola for which highly resolved phylogenetic trees were available (unpublished data) 12 . However, we note that the scaling trends within given lineages may depart from the global across-species trends shown here, especially in lineages adapted across environments.…”
Section: Methodsmentioning
confidence: 84%
See 3 more Smart Citations
“…Notably, genus-by-genus analyses produced comparable patterns, as did phylogenetically controlled tests within lineages for Acer, Plantago and Viola for which highly resolved phylogenetic trees were available (unpublished data) 12 . However, we note that the scaling trends within given lineages may depart from the global across-species trends shown here, especially in lineages adapted across environments.…”
Section: Methodsmentioning
confidence: 84%
“…However, despite the strong potential importance of such trends, there have not been any previous conclusive tests for the scaling of vein traits with leaf size across species. Data from three previous studies with ten or fewer species showed a negative scaling of major vein density with leaf size, and minor vein density was independent of leaf size 8,12,13 . A further study using automated analyses of low-resolution images reported vein density to be independent of leaf size across 339 species 14 ; however, that study measured only a fraction of the vein system and did not distinguish among vein orders 14 and thus, did not allow a conclusive test of general scaling of vein traits.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Previous studies of adaptation to these conditions within species or across closely related species within given lineages have shown increased vein densities, and thus shorter interveinal distances [76][77][78][79]. This higher vein density would permit greater g s and higher A during periods with high water availability, to compensate for low CO 2 .…”
Section: Hypothesis For a Central Importance Of Hydraulics In C 4 Evomentioning
confidence: 93%